2020
DOI: 10.1101/2020.12.07.20245456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) combined with cognitive training in adolescent boys with ADHD: a double-blind, randomised, sham-controlled trial

Abstract: BackgroundTranscranial direct current stimulation (tDCS) could be a side-effect free alternative to psychostimulants in Attention-Deficit/Hyperactivity Disorder (ADHD). Although there is limited evidence for clinical and cognitive effects, most studies were small, single-session, and stimulated left dorsolateral prefrontal cortex (dlPFC). No sham-controlled study has stimulated right inferior frontal cortex (rIFC), which is the most consistently under-functioning region in ADHD, with multiple sessions of anoda… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 117 publications
(171 reference statements)
0
11
0
Order By: Relevance
“…There was also no superior effect of real versus sham tDCS on a large battery of executive functions. While side effects did not differ between groups, the real tDCS group had worse adverse events related to mood, sleep and appetite (43). To conclude, there is large heterogeneity in tDCS studies with respect to study designs, stimulation parameters and site of stimulation which makes comparability between studies difficult.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 82%
See 1 more Smart Citation
“…There was also no superior effect of real versus sham tDCS on a large battery of executive functions. While side effects did not differ between groups, the real tDCS group had worse adverse events related to mood, sleep and appetite (43). To conclude, there is large heterogeneity in tDCS studies with respect to study designs, stimulation parameters and site of stimulation which makes comparability between studies difficult.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 82%
“…One study found an improvement with transcranial random noise stimulation (tRNS) of left DPFC and right IFC compared to tDCS of left DLPFC combined with cognitive training on ADHD symptoms in 19 patients (42). However, the largest study that tested 15 sessions of tDCS of right IFC in 50 ADHD patients found no improvement compared to sham in clinical symptoms and even an improvement with sham relative to tDCS (43).…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%
“…Of the nine RCTs, overall risk-of-bias was rated as "high" in five studies [32,33,36,52,56]; two with "some concerns" [37,39], and two with "low" [29,38] (see Supplementary Material S2). The non-randomised, controlled clinical trial was rated with moderate risk of bias [54].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Two double-blind RCTs applied tDCS to the inferior frontal cortex (IFC). The largest RCT in CYP with ADHD (n = 50) administered 15 sessions of anodal or sham tDCS to the right-IFC with concurrent cognitive training [39]. Compared to sham, the tDCS group showed significantly higher parent-rated ADHD symptoms immediately after stimulation, but not at a 6-months follow-up.…”
Section: (B) Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
See 1 more Smart Citation